A comparative transgene expression study between a protaplex and a rotaplex embedded lipid‐nano particles in murine derived dendritic cell. Issue 2 (2nd May 2018) - Shaheen, Sharif M.; Azad, A.K.; Mustafezur Rahman, M.; Uddin, Md. Jashim
Abstract: Gene therapy depends on the perfect DNA delivery to the nuclear subdomain, where DNA should be orchestrated in a lipid based programmed packaging, like multi‐functional envelope type of nano device (MEND) and tetra lamellar multi‐functional envelope type of nano device (T‐MEND) published elsewhere. In both the packaging system, DNA has to make a complex (core) with a cationic polymer. It is important how about the effect of such a DNA/condenser core inside the programmed‐packaging reflects the transgene expression. Here we compared transgene expression of a firefly luciferase gene from both the protaplex (protamine‐DNA) and rotaplex (polyrotaxane‐DNA), packaged in MENDs. Dendritic cells were transfected with these nanoparticles and transgene expression, cell viability as well as antigen presentations were measured. Transgene expression from the MEND of protaplex was significantly higher in JAWs‐II cell (dendritic cell line) and bone marrow dendritic cell. Cell viability and antigen presentations from the protaplex were also prompt and better than that of polyplex, when T‐MEND package systems containing protaplex and rotaplex, were compared. Confocal microscopic studies of fluorescently labeled plasmid DNA reflected the evidence of ease decondensation of DNA from the protaplex than that of a rotaplex. Our results suggest that a natural DNA condenser (protamine in protaplex) prefers transgene expression better to those of synthetic polycationic condenser (polyrotaxane in rotaplex). Abstract : Gene therapy depends on good DNA delivery to the nucleus, where DNA should be orchestrated in a lipid based‐packaging, like multi‐functional‐envelope‐type nano device and tetra‐lamellar‐multi‐functional‐envelope‐type nano device published elsewhere. DNA/condenser affects directly on the DNA release from a non‐viral vector like multi‐functional‐envelope‐type nano device and tetra‐lamellar‐multi‐functional‐envelope‐type nano device. Our results suggest that a natural DNA condenser (protamine in Protaplex) prefers transgene and antigen expression better to those of synthetic poly cationic condenser (polyrotaxane in Rotaplex) in bone marrow‐derived dendritic cell (BMDC).